Factors influencing COVID-19 vaccination: a study performed in fall of 2021 among Romanian adults from general practitioners - Cristina Florina Roșian; Simona Mirel; Mira Florea; Romana Vulturar; Ovidiu Stan; Milena Man; Lucia Maria Lotrean (Humanities & Social Sciences Communications)
Abstract This study was performed during the fourth wave of COVID-19 cases in Romania and had three objectives. First, it has assessed the opinions regarding COVID-19 vaccination during a severe wave of the pandemic among Romanian adults. Second, it aimed to get insights into their behavior regarding vaccination and factors influencing it. Last, but not least, intention regarding future vaccination and associated factors were assessed. A cross-sectional study was conducted in 3 general practitioners’ (GP) medical offices, in one city from Cluj county, Romania, from October 2021 to December 2021. The study involved 502 Romanian adults who filled in an anonymous questionnaire. 71.7% of the participants were vaccinated and most of those patients were vaccinated with a vaccine that was given in several doses and received the second dose-45% or even the third one-33.1%. The results of the logistic regression analyses show that there were no age, gender or educational level differences regarding vaccination status. On the other hand, people who got the disease (OR = 0.533, CI = 0.315–0.903) or thought the vaccine provoked sterility for women (OR = 0.635, CI = 0.453–0.888) were less likely to get vaccinated. People who were more convinced about the efficacy and safety of the vaccine (OR = 1.718, CI = 1.338–2.206) as well as its importance for getting back to normality (OR = 2.151, CI = 1.705–2.713) were more likely to get vaccinated. A percentage of 42.3% of those who were not vaccinated said they do not know if they would get vaccinated, 33.1% of them said they would not get vaccinated, while around one quarter declared their intention to get vaccinated in the near future. The results of the logistic regression analyses show that there were no differences regarding the intention to get vaccinated based on age, gender or educational level, but people who had stronger beliefs that the vaccine is not protecting against the disease so is not useful were less convinced that they will get vaccinated (OR = 0.600, CI = 0.402–0.894), while those who believe it will help our return to normality were more likely to declare their intention to get vaccination (OR = 2.355, CI = 1.544–3.592). The study gives insights into attitudes, behavior and intention related to COVID-19 vaccination among Romanian adults during a challenging period of COVID-19 pandemic. The results have implications for public health, organization of health communication campaigns and pandemics management.